Momentum. Umění a kosmopolitní modernita - Szerszynski, Bronislaw (Masaryk University Press, 2018)
Title in English: Momentum. Art and Cosmopolitan Modernity. This book attempts to capture the momentum, a moment of transformation, where the complex processes related to the expansion of heterogeneous cosmopolitan modernity intersect and converge, processes that influence and change both Euro-American civilisation and the planet as a whole, and along the way transform the state, economic, cultural and social arrangement, the practises and the notions used in order to understand our existence in the world. The authors of the studies that make up this publication look at the problem from several selected aspects falling within the domains of sociology, culture and new media art, which have in common an effort to put current phenomena into more general and more profound social, political and cultural contexts. They strive to avoid presentism in order to observe the processes gathered under the umbrella of "cosmopolitan modernity" from the point of view of the longue durée.